Nurse interventions in clinical management that promote quality of care: scoping review - Carla Silva; Vera Magalhães; Vanessa Santos; Susana Miguel; Patrícia Pontífice-Sousa; Rita Marques (Millenium)
Introduction: Nurse interventions in clinical management can take different forms, and there is a connection between management and care provision. Despite the recognised importance of clinical management for the quality of care, there are still gaps in knowledge about the most effective and efficient interventions in this field.